PENGARUH PEMBERIAN ASUPAN GIZI SEIMBANG TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA DINI - Deviea Ajeng Rohima; Aip Saripudin; Eti Nurhayati; Diani Magasida (AWLADY : Jurnal Pendidikan Anak, 2023)
Balanced nutrition is the daily dietary composition that contains nutrients in the type and amount that suits the needs of the body. Giving balanced nutrition intake plays an important role in child growth and maturation development of brain nervous system that became the center of cognitive abilities of children.lack of some nutrients can have a negative impact on the process of growth and brain development of children. Early childhood requires more nutritional intake than adults, as children are still in the growth and development stage. Early childhood is a golden age for the development of one of them cognitive development. The type of research used is ex post facto research using a quantitative approach. While the purpose of the study was to determine the intake of balanced nutrition provided by parents to children, to know the cognitive development of children, and to determine the effect of balanced nutrition intake on early childhood cognitive development. from the results of research, it is obtained data that the provision of balanced nutrition intake in TK Budi Asih IX entered in good category with the percentage value of 76,75% is at intervals of 70%-79%, early childhood cognitive development in TK Budi Asih IX enter in very good category with the percentage value of 89% is at intervals of 80%-100%, and the influence of balanced nutrition intake to early childhood cognitive development in TK Budi Asih IX is 0,736 (73,6%) which means the provision of balanced nutrition has a significant influence on early childhood cognitive development in TK Budi Asih IX Cipinang Village Rajagaluh District Majalengka Regency.